Tourism as a Driver of Rural Socio-Economic Development: The Case of Boabeng-Fiema Monkey Sanctuary - Baah-Mintah, Richard; Owusu-Adjei, Ellen; Hiamey, Stephen E (Journal of Tourism Management Research, 2022)
Many countries especially developing ones like Ghana see tourism as a conduit for socio-economic development. This paper aims to examine stakeholders’ perceptions of the socio-economic effect of the Buabeng-Fiema Monkey Sanctuary. To achieve this aim, research was carried out into the role of tourism (a Monkey Sanctuary) in promoting rural socio-economic development in Ghana. The systematic sampling and purposive sampling methods were used to select 265 household heads and 11 key informants respectively from the Boabeng and Fiema communities. The questionnaire, interview guide, and observation were mainly used to collect data from respondents. The main finding reveals a community’s acceptance of tourism as having the potential to promote rural socio-economic development. However, this potential is challenged by the activities of the monkeys, destroying farm crops and properties coupled with an infrastructural deficit in the area. Implications are outlined for policymakers and the management of the wildlife sanctuary.